Development of a Space Rental Website Using Design Thinking - Cantika Nur Previana; Risqy Siwi Pradini; Jenike Gracelya Noke (Institut Teknologi, Sains, dan Kesehatan RS.DR. Soepraoen Kesdam V/BRW, 2024)
The large number of events held in Malang City has created a need for a place to hold these events. This need opens opportunities for developing venue rental applications to make it easier to search and book rooms according to the needs of each event. This research develops